Analisis Korelasional Antara Pendapatan Finansial, Peningkatan Jabatan, dan Kepuasan Kerja - Wita Farla; Lina Dameria Siregar; Umar Hamdan (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2022)
The purpose of this study was to determine the correlation between financial income to job satisfaction and job promotion to job satisfaction. The type of data used in this study is primary data. Research data was collected by questionnaire. The population in this study were lecturers at one of the universities in South Sumatra. Samples were taken as many as 90 people using random sampling. The analytical technique used in this research is descriptive analysis and correlation analysis. The results of this study are financial income has a positive relationship with job satisfaction, as well as job promotion which also has a positive relationship with job satisfaction. Therefore, it is expected that the job satisfaction felt by lecturers can be maintained and even improved. This study only uses two independent variables, for further research can add other variables that have not been included in this study and examine the correlation of these variables to job satisfaction.Keywords: financial income, job promotion, job satisfaction